BEBERAPA FAKTOR YANG MEMPENGARUHI FLUKTUASI HARGA WIRE ROD - , Danial ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wire rod is a steel building materials which are widely used in the building construction industry. Wire rod price volatility increases the risk to the business world, particularly the steel industry. The purpose of this research is to determine the factors that influence Wire rod price changes. Factors examined its effect on Wire rod price is the price of Hot rolled, the price of coal, cement consumption of the United States and United States steel import. The method used in this research is multiple linear regression model using the software PASW statistics 18. From the analysis in this research note that the price of hot rolled, the price of coal, cement consumption in the United States as well as United States steel import trade has a positive relationship and that four variables significantly affects the price of wire rod with Î± = 5%.